J04 A prospective observational study of the frequency of single nucleotide polymorphisms (SNP) in patients with huntington's disease (hd). (September 2018) - Claassen, Daniel; Edmondson, Mary; Reilmann, Ralf; Svrzikapa, Nenad; Longo, Kenneth; Goyal, Jaya; Hung, Serena; Panzara, Michael
Abstract : Background: Expansion of a cytosine-adenine-guanine (CAG) triplet repeat in the Huntingtin (HTT) gene causes HD through production and accumulation of mutant HTT (mHTT) protein, leading to progressive loss of neurons in the brain. The pathogenic CAG repeat has been linked to certain SNPs, allowing the possibility of targeting SNPs to lower mHTT protein without impacting wild-type HTT (wtHTT) protein, which is essential for neuronal development and homeostasis. Aim: To determine the frequency of the thymine (T) variant of rs362307 (SNP1) or rs362331 (SNP2) on the same HTT allele as the pathogenic CAG triplet repeat expansion in patients with HD. Methods: Across 7 US sites, HD patients (aged 25–65 years) with United HD Rating Scale Total Functional Capacity scores of 7–13 are eligible to enroll. Blood samples are collected at 1 clinic visit and processed in 3 steps at a central laboratory. The first step confirms the number and size of CAG repeats in DNA samples, using polymerase chain reaction and Bioanalyzer, respectively. The second step determines the presence of SNPs (heterozygosity) via Sanger sequencing. Finally, samples with CAG repeats ≥36 and SNP heterozygosity are assessed to determine whether the SNP is present (phased) on the mHTT allele using RNA samples and a long-range sequencing investigational assay. Results: A total of 203 HD patients have been enrolled and 199 DNA samples processed. All patients had confirmation of HD diagnosis with ≥36 CAG repeats (median, 44.36; range, 38–62). Heterozygosity was identified in 144 (72%) patients. Phasing results are available for 104 patients, of which, 88 (85%) had SNP1 (n=40), SNP2 (n=21), or both (n=27) present on the mHTT allele. Conclusions: Results indicate that over 70% of HD patients have the targeted SNPs, which is consistent with previous reports. The ability to identify and target SNPs associated with the CAG repeat may allow personalized therapy. Final phasing results will be presented.